Vibration Analysis of Reinforced Concrete Simply Supported Beam versus Variation Temperature - Hanbing Liu; Hua Wang; Guojin Tan; Ziyu Liu; Yongchun Cheng (Shock and Vibration)
It is well known that temperature has great influence on modal characteristics of bridges. The relationship between them has been studied by using statistical mathematics, numerical analysis, and field’s monitoring methods, which have relatively narrow applicability. Therefore, it is necessary to analyze their relationship theoretically. In this paper, the relationship between temperature and modal characteristics of the simply supported beam is investigated based on theoretical calculation method. Firstly, the temperature field is analyzed to find out the main factors that lead to the changes of modal characteristics. Secondly, the dynamic equations of simply supported beam under the effect of temperature are established. Next, a test beam is constructed to validate the proposed calculation method experimentally. The calculated results are in good agreement with those from the experiment. Finally, the proposed method is successfully applied to real engineering.